2016
DOI: 10.1007/s00436-016-5166-3
|View full text |Cite
|
Sign up to set email alerts
|

In silico cloning and B/T cell epitope prediction of triosephosphate isomerase from Echinococcus granulosus

Abstract: Cystic echinococcosis is a worldwide zoonosis caused by Echinococcus granulosus. Because the methods of diagnosis and treatment for cystic echinococcosis were limited, it is still necessary to screen target proteins for the development of new anti-hydatidosis vaccine. In this study, the triosephosphate isomerase gene of E. granulosus was in silico cloned. The B cell and T cell epitopes were predicted by bioinformatics methods. The cDNA sequence of EgTIM was composition of 1094 base pairs, with an open reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…There is no information regarding TPI as a vaccine target in toxoplasmosis. However, the present data regarding the activation of the immune system and immunomodulatory properties by this stage-specific protein and the recent suggestions for TPI as a vaccine target in helminth and Leishmania parasites might further reinforce the selection of this protein as a promising vaccine candidate against toxoplasmosis [96][97][98][99].…”
Section: Triose-phosphate Isomerase (Tpi)mentioning
confidence: 62%
“…There is no information regarding TPI as a vaccine target in toxoplasmosis. However, the present data regarding the activation of the immune system and immunomodulatory properties by this stage-specific protein and the recent suggestions for TPI as a vaccine target in helminth and Leishmania parasites might further reinforce the selection of this protein as a promising vaccine candidate against toxoplasmosis [96][97][98][99].…”
Section: Triose-phosphate Isomerase (Tpi)mentioning
confidence: 62%
“…Specific epitopes determine the specificity of antigens ( 33 ). Therefore, epitope prediction is particularly important in the study of protein structure and function, and for the diagnosis of diseases and the design of vaccines ( 34 ). The present study found that there were seven potential B-cell epitopes in Eg-TSP11, among which the random coil regions were 227–240 (amino acid sequence: WQYGPPRFTNGAHN) and 210–219 (amino acid sequence: LTGWPTDQYQ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several of the hereidentified proteins have been proposed as vaccine candidates against E. granulosus. 4,45,46 Among them, Eg.P29-also known as endophilin B1 (#17 in our set) -revealed significant protective activity against secondary infection in mice, 47 as well as against primary infection in sheep, 48 inducing in both cases roughly 95% protection levels. According to our classification, this protein is "unique" (US: 0.24) and highly antigenic (ANTIGENpro score: 0.94), showing an AAR value (42.2) similar to the one obtained for the whole PSEx proteome.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 58 proteins we reported for PSEx, 36 of them were previously identified in at least one of the abovementioned studies, while 22 proteins were described for the first time in the present work (Table ). Furthermore, several of the here‐identified proteins have been proposed as vaccine candidates against E. granulosus . Among them, Eg.P29—also known as endophilin B1 (#17 in our set)—revealed significant protective activity against secondary infection in mice, as well as against primary infection in sheep, inducing in both cases roughly 95% protection levels.…”
Section: Discussionmentioning
confidence: 99%